Tropical cyclone Wind Pump induced chlorophyll-a enhancement in the South China Sea: A comparison of the open sea and continental shelf - Li, Ying; Tang, Danling (Frontiers in Marine Science, 2022)
The continental shelf (water depth<200m) and open sea (water depth>200m) region, have different ocean physical and environmental responses to tropical cyclones (TC). The present study firstly compared the grid-based maximum response (GMR) of sea surface chlorophyll a (Chl-a) to 178 TC cases between the continental shelf and open sea in the South China Sea (SCS) during 1998-2020, using multiple-satellite data. For all TC cases, the average Chl-a increases by 0.13 mg/m3, with the maximal increase reaching up to 1.21 mg/m3. The comparisons between the pre- and post-TC periods show that Chl-a in the post-TC period increases by 0.18 mg/m3 (115%) and 0.07 mg/m3(57%) in the continental shelf and open sea, respectively. The temporal variation of Chl-a both experienced a slight decrease in the first 3 days after TC and then began to rise. In both regions, TC-induced Chl-a enhancement (Chl_en) strongly depends on TC intensity which was measured by the maximum wind speed and translation speed. The strong and fast-moving TCs and weak and slow-moving TCs both induce the largest Chl_en in the continental shelf region. However, in the open sea, the largest Chl_en was induced by the strong and slow-moving TCs. Overall, our results reveal that the TC wind pump’s effects on Chl-a enhancement are stronger in the continental shelf region than that in the open sea.